Applications of induced pluripotent stem cell technologies in spinal cord injury - Nagoshi, Narihito; Okano, Hideyuki (Journal of neurochemistry, 2017)
Numerous basic research studies have suggested the potential efficacy of neural precursor cell (NPC) transplantation in spinal cord injury (SCI). However, in most such studies, the origin of the cells used was mainly fetal tissue or embryonic stem cells, both of which carry potential ethical concerns with respect to clinical use. The development of induced pluripotent stem cells (iPSCs) opened a new path toward regenerative medicine for SCI. iPSCs can be generated from somatic cells by induction of transcription factors, and induced to differentiate into NPCs with characteristics of cells of the central nervous system. The beneficial effect of iPSC‐derived NPC transplantation has been reported from our group and others working in rodent and non‐human primate models. These promising results facilitate the application of iPSCs for clinical applications in SCI patients. However, iPSCs also have issues, such as genetic/epigenetic abnormalities and tumorigenesis because of the artificial induction method, that must be addressed prior to clinical use. The selection of somatic cells, generation of integration‐free iPSCs, and characterization of differentiated NPCs with thorough quality management are all needed to address these potential risks. To enhance the efficacy of the transplanted iPSC‐NPCs, especially at chronic phase of SCI, administration of a chondroitinase or semaphorin3A inhibitor represents a potentially important means of promoting axonal regeneration through the lesion site. The combined use of rehabilitation with such cell therapy approaches is also important, as repetitive training enhances neurite outgrowth of transplanted cells and strengthens neural circuits at central pattern generators. Our group has already evaluated clinical grade iPSC‐derived NPCs, and we look forward to initiating clinical testing as the next step toward determining whether this approach is safe and effective for clinical use. This article is part of the mini review series “60th Anniversary of the Japanese Society for Neurochemistry”. Since the development of induced pluripotent stem cells (iPSCs), we have demonstrated the efficacy of iPSC‐derived neural precursor cells (NPCs) in animal models of spinal cord injury (SCI), and challenged safety issues such as tumorigenicity. Moreover, we have advocated importance of combinatory therapy to enhance regeneration in SCI, especially at chronic phase. We are developing and characterizing clinical grade iPSC‐derived NPCs, and the application for SCI patients will start shortly. This article is part of the mini review series “60th Anniversary of the Japanese Society for Neurochemistry”.